1990
DOI: 10.1002/jso.2930430111
|View full text |Cite
|
Sign up to set email alerts
|

Safety of EEA staplers for anastomosis between upper esophagus and the gastric tube

Abstract: The EEA stapling devices used for intrathoracic anastomosis between the upper esophagus and the gastric tube in patients with carcinoma of the thoracic esophagus were evaluated, and the results were compared with those of an antesternally reconstructed esophagus. These approaches were both used by the same surgical team. An intrathoracic anastomosis using the EEA stapler was made in 53 patients with carcinoma of the thoracic esophagus. Minor anastomotic leakage occurred in five patients (9.4%). Good results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This procedure is an adaptation of intrathoracic reconstruction using a narrow gastric tube after thoracic esophagectomy for esophageal cancer 9 . The procedure has several advantages: 5 (i) it is technically simple and the operation time is short; (ii) food tolerance is good and delayed emptying or reflux esophagitis is rare; and (iii) the procedure does not sacrifice the proximal part of the jejunum, which is important for the digestion and absorption of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is an adaptation of intrathoracic reconstruction using a narrow gastric tube after thoracic esophagectomy for esophageal cancer 9 . The procedure has several advantages: 5 (i) it is technically simple and the operation time is short; (ii) food tolerance is good and delayed emptying or reflux esophagitis is rare; and (iii) the procedure does not sacrifice the proximal part of the jejunum, which is important for the digestion and absorption of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Our technique is an application of intrathoracic reconstruction in which a gastric tube was used after thoracic esophagectomy for esophageal cancer [18]. De spite negative pressure in the thoracic cavity, gastric tube reconstruction after esophagocardiectomy for cancer of the gastric cardia or abdominal esophagus does not result in reflux esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that recent advances of the EEA sta pling device reduced the incidence of anastomotic leakage [18,19]. It is considered that the intrathoracic anastomo sis using the EEA stapling device is a safe procedure.…”
Section: Discussionmentioning
confidence: 99%